Modelagem e controle do sistema de nível de aço no molde de uma planta de lingotamento contínuo - Sanchotene, Fábio de Borba (2009)
This document describes the results of the development and simulating of a complete mould level control system model of a real continuous casting plant, establishing a specific study of this model, including the disturbances inherent on this kind of industrial process and presenting the conception and application of different controller strategies, foreseeing a optimized control to the simulated process. The study considers: the procedures for obtaining a reliable model (by means of mathematical construction and identification), the validation of the final process model obtained and demonstrates the disturbances present on the real process also considering the application (on simulated environment) of two specific control techniques: generalized predictive control (GPC) and conventional PID, including the required adaptations, dependant of the effect reduction complexity, including on these adaptations the usage of the Recursive Least Square Estimator (RLS)